Predictors of well-being and quality of life in men who underwent radical prostatectomy: longitudinal study - Adilson Edson Romanzini; Maria da Graça Pereira; Caroline Guilherme; Adauto José Cologna; Emilia Campos de Carvalho (Universidade de São Paulo, 2018)
ABSTRACT Objective: to identify socio-demographic, clinical and psychological predictors of well-being and quality of life in men who underwent radical prostatectomy, in a 360-day follow-up. Method: longitudinal study with 120 men who underwent radical prostatectomy. Questionnaires were used for characterization and clinical evaluation of the participant, as well as the instruments Visual Analog Scale for Pain, The Ways of Coping Questionnaire, Hospital Depression and Anxiety Scale, Satisfaction with Social Support Scale, Marital Satisfaction Scale, Subjective Well-Being Scale and Expanded Prostate Cancer Index. For data analysis, the linear mixed-effects model was used. Results: the socio-demographic factors age and race were not predictors of the dependent variables; time of surgery, problem-focused coping, and anxiety were predictors of subjective well-being; pain, anxiety and depression were negative predictors of quality of life; emotion-focused coping was a positive predictor. Marital dissatisfaction was a predictor of both variables. Conclusion: predictor variables found were different from the literature: desire for changes in marital relationship presented a positive association with quality of life and well-being; emotion-focused coping was a predictor of quality of life; and anxiety was a predictor of subjective well-being.